2013
DOI: 10.5923/j.fs.20120206.02
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Land Use/Land Cover Changes in a Section of Niger Delta, Nigeria

Abstract: Re mote Sensing and GIS offer quick and efficient approach to the classification and mapping of land use/land cover changes over space and time. Info rmation on changes in resource classes, direction, area and pattern of land use-land cover classes form the basis for future planning. Specifically, the land use/land cover types for the years 1986 and 2008 were studied and compared. The data products used in the study are Landsat TM imagery of 1986 and Nigeriasat-1 imagery of 2008. The data sets were put into Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This has led to continuous changes in both land-cover and land-use patterns of the region. It has also been shown that expansion in the oil exploration and exploitation activities had increased pressure with heavy impact on the natural ecosystems as a result of oil spill incidences (Abbas 2012). Records have shown that most of the oil pollution from oil operations in the regions has remained in the environment for many years without clean-up and yet to recover the lost natural vegetation (UNEP 2011).…”
Section: Land Use and Land Covermentioning
confidence: 99%
“…This has led to continuous changes in both land-cover and land-use patterns of the region. It has also been shown that expansion in the oil exploration and exploitation activities had increased pressure with heavy impact on the natural ecosystems as a result of oil spill incidences (Abbas 2012). Records have shown that most of the oil pollution from oil operations in the regions has remained in the environment for many years without clean-up and yet to recover the lost natural vegetation (UNEP 2011).…”
Section: Land Use and Land Covermentioning
confidence: 99%
“…The Niger Delta also has large oil and gas deposits which have been heavily exploited for decades [48], contributing substantially to mangrove forest loss [14]. The expansion of the oil industry typically involves the creation of canals for exploration and access, causing contamination of freshwater systems with seawater and destroying local ecosystems [49]. In addition, since the 1970's there have been multiple unrecovered oil spills [49], causing widespread damage to the mangrove forest [48].…”
Section: Niger Delta Nigeriamentioning
confidence: 99%
“…The expansion of the oil industry typically involves the creation of canals for exploration and access, causing contamination of freshwater systems with seawater and destroying local ecosystems [49]. In addition, since the 1970's there have been multiple unrecovered oil spills [49], causing widespread damage to the mangrove forest [48]. Estimates suggest that between 9 and 13 million barrels of oil have been spilled in the Niger Delta since 1958 [50].…”
Section: Niger Delta Nigeriamentioning
confidence: 99%
See 2 more Smart Citations